Assistance in Library Management Based on the Senayan Library Management System (SLiMS) at SMA Darut Taqwa Purwosari - Hasan Syaiful Rizal; Jakfar Syodik; Mochamad Hasyim (LPPM Universitas Yudharta Pasuruan, 2022)
This community service program is carried out in the form of library management assistance based on SLiMS at Darut Taqwa High School, Purwosari Pasuruan. Libraries have an important role in building a learning community, as well as school libraries. The school library is a strategic educational facility, because apart from supporting learning activities. The school library is also one of the barometers of school quality standards. Darut Taqwa High School was chosen as a mentoring partner on the basis that this institution is one of the institutions in Pasuruan Regency that has received an A (excellent) accreditation. However, the quality standard of library administration is still far from the national library standard. This assistance uses the participatory approach. The steps for implementing this assistance are focused on 1) selecting the assisted person, 2) installing the SLiMS application, 3) the SLiMS operation tutorial, and 4) managing the SLiMS-based library. The results of this assistance are 1) the availability of library staff at Darut Taqwa High School who understands SLiMS-based library management, 2) the availability of a SLiMS-based library automation system, 3) the creation of a system for managing library materials, members, and library administration, and 4) the creation of a good library layout that is quite close to the minimum standard of the national library.